2019
DOI: 10.1002/mgg3.802
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutation in the matrix metallopeptidase 2 coding gene associated with intrafamilial variability of multicentric osteolysis, nodulosis, and arthropathy

Abstract: Background MONA, which stands for a spectrum of Multicentric Osteolysis, subcutaneous Nodulosis, and Athropathia, is an ultra rare autosomal recessive disorder caused by mutations in the matrix metallopeptidase 2 (MMP2) gene. To date only 44 individuals, carrying 22 different mutations have been reported. Here we report on two brothers with identical homozygous MMP2 gene mutations, but with clearly different phenotypes. Methods Genomic DNA was isolated from the affected brothers and the parents. An iliac crest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 12 publications
(28 reference statements)
0
14
0
Order By: Relevance
“…A similar pattern usually occurs in the feet (2,3,5,(8)(9)(10)(11)(12). Non-skeletal manifestations include facial dysmorphism and oral (2,3,11,13,14,15), dermatologic (2,9,12,(14)(15)(16), ophthalmological and cardiac manifestations (2,3,7,11,13,15,17,18).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…A similar pattern usually occurs in the feet (2,3,5,(8)(9)(10)(11)(12). Non-skeletal manifestations include facial dysmorphism and oral (2,3,11,13,14,15), dermatologic (2,9,12,(14)(15)(16), ophthalmological and cardiac manifestations (2,3,7,11,13,15,17,18).…”
Section: Introductionmentioning
confidence: 94%
“…MONA syndrome is inherited through an autosomal recessive manner. It is believed that only 46 patients with 24 different variants in MMP2 are published (3,7). And that only four patients with two variants in MMP14 have been reported (2).…”
Section: Introductionmentioning
confidence: 99%
“…As an extremely rare genetic disease with only 46 cases and 23 mutations from 28 families reported in the literature, no exact epidemiological statistics of MONA, have been described ( 34 ). Typical clinical manifestations of MONA consist of extensive osteopenia and osteolysis (most prominent in carpal and tarsal bones), progressive osteoarthropathy, and subcutaneous nodules on the palms and soles ( 35 ).…”
Section: Mmp2 In Hereditary Skeletal Dysplasiamentioning
confidence: 99%
“…Vanatka et al ( 37 ) reported a case of MONA with long-term follow-up, in which the pathological changes of the bones over a 23-year period were striking and the pattern of bone loss was progressive and periarticular. Furthermore, ~75% of mutations from the reported MONA cases occur in the catalytic domain or have detrimental effects on its catalytic function, resulting in impaired MMP2 activity ( 34 , 38 ). Consequently, although individual differences in clinical manifestations exist among MONA patients, almost all of them contain signs of bone loss and osteolysis, indicating that loss of MMP2 accounts for impaired bone integrity and mineral homeostasis during skeletal growth and development.…”
Section: Mmp2 In Hereditary Skeletal Dysplasiamentioning
confidence: 99%
“…This phenotype has been attributed largely to the importance of MMP14 in collagen turnover and bone remodeling [14,15]. While mice deficient in MMP2 exhibit relatively mild skeletal defects which result in reduced bone mineralization and joint erosion, mutations in human MMP2 and MMP14 cause the severe connective tissue syndromes known as MONA (Multicentric Osteolysis, subcutaneous Nodulosis, and Athropathia) and Winchester Syndrome, respectively [16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%